Stone - Vincent, Patrick (Romanticism on the Net, 2023)
This essay draws on fifteen exhibits in RÊVE (Romantic Europe: The Virtual Exhibition) as well as on a sample of texts and paintings in order to show the significance of stones to European Romanticism, contributing among other things to the age’s sentimental and Gothic cultures, to its development of landscape aesthetics and tourism, and to its historicism and new understanding of revolution in natural history and in politics. Using John Ruskin as a narrative thread, the essay focuses on the period’s quest to ascribe agency to stones and stone-related artefacts through imaginative sympathy and affect. While stone long stood for solidity and permanence in Western culture, it also came to be seen during the Romantic period as a fragile, even vital thing.